Aircraft wind measurements to assess a coupled WRF‐CALMET mesoscale system. (31st October 2013) - Gioli, Beniamino; Gualtieri, Giovanni; Busillo, Caterina; Calastrini, Francesca; Gozzini, Bernardo; Miglietta, Franco
ABSTRACT Long term aircraft observations of wind magnitude along an ∼250 km flight track in central Italy, performed over 1.5 years, are compared with the output of an existing mesoscale prognostic‐diagnostic (WRF‐CALMET) model chain aimed at assessing wind potential maps at regional scale. Aircraft measurements are used to evaluate model performance along spatial and temporal transects at moderate altitude from the ground (∼75 m), where observational frameworks are rarely available. Spatial wind analysis was capable of assessing overall model performance, while highlighting some limitations: the implemented models have better performance in inland areas with respect to coastal areas, while they are capable of representing diurnal variability in all regions correctly. Overall agreement is within 3% in the cold season and 16% in the warm season, while the greatest differences, above 30%, are obtained in coastal areas in the summer. The hypothesis supporting these results is that summer sea breeze regimes that develop consistently from the coast through the interior land are not entirely resolved from mesoscale modelling. Finally, the model performance and limitations related to complex orography are highlighted. This study demonstrates the added value that may derive from aircraft wind measurements as an additional observational framework for applied meteorology studies.